Ultrasensitive detection of amlodipine using plasmonic optical fiber sensors enhanced with graphene oxide and chitosan nanocomposite - Fidan T. Sedeeq; Hassan Nasiri; Karim Abbasian; Hadi Khodaei (Scientific Reports)
Abstract In this study, we introduce an innovative reflective fiber optic sensor platform for detecting amlodipine (AML) concentrations based on surface plasmon resonance (SPR). The sensor architecture features a reflective fiber coated with a thin layer of gold to induce SPR, while a graphene oxide/chitosan (GOCH) composite, applied via spin-coating, serves as the selective sensing layer for AML. The incorporation of a nanocomposite enables the generation of resonance dips in the spectral output, each demonstrating different sensitivities to AML concentration variations. These resonance wavelength shifts allow for accurate quantification of AML by employing Langmuir and Sips adsorption isotherm models. Experimental analysis reveals a remarkable sensitivity of 2315.2 nm/µM for AML detection, alongside a strong binding affinity of 60.12 µM⁻1. The proposed sensor also demonstrates excellent stability and is well-suited for convenient packaging, highlighting its potential for remote and practical sensing applications.